2011
DOI: 10.2147/ijwh.s23124
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions to prevent mother-to-child transmission of HIV in Southern Ethiopia

Abstract: BackgroundIn Ethiopia, Progress in Reducing Mother-to-Child-Transmission (PMTCT) of human immunodeficiency virus (HIV) is being curtailed by behavioral and cultural factors that continue to put unborn children at risk, and mother-to-child transmission is responsible for more than 90% of HIV infection in children. The objective of this study was to assess PMTCT services by examining knowledge about reducing vertical transmission among pregnant women.MethodsA multistaged sampling institution-based survey was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 11 publications
4
17
2
Order By: Relevance
“…A study conducted in Ivory Coast revealed that mothers were afraid of being scolded at by health staff and that health workers were not attending to them when they had come for follow-up visits [39]. In Ethiopia, a study revealed that poor monitoring of PMTCT services by health workers was one of the reasons to poor followups in PMTCT program because health facilities did not have registered information on HIV-1-positive mothers who enrolled in PMTCT but failed to return for follow-up care [13]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted in Ivory Coast revealed that mothers were afraid of being scolded at by health staff and that health workers were not attending to them when they had come for follow-up visits [39]. In Ethiopia, a study revealed that poor monitoring of PMTCT services by health workers was one of the reasons to poor followups in PMTCT program because health facilities did not have registered information on HIV-1-positive mothers who enrolled in PMTCT but failed to return for follow-up care [13]. …”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in Malawi and Zimbabwe showed that many existing programs suffered from high attrition rates and incomplete PMTCT followup due to the fact that many women, especially in rural areas, delivered at home rather than at a health facility [11, 20]. A study conducted in Ethiopia revealed that only 16% of births were attended by skilled personnel while in Uganda a study revealed that 71 (95.9%) of HIV-1-positive women did not return for an institutional delivery [13, 35]. Cultural influences, poor socioeconomic status, and fear of the stigma associated with an HIV-1-positive status are factors that influence choice of delivery location [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings that ANC use was greater among women with higher knowledge of MTCT are consistent with this prior cross-sectional survey that reported higher knowledge of MTCT among women in a healthcare setting compared with national EDHS estimates. Conversely, a study conducted in 2009 among pregnant women attending prevention of MTCT services in Southern Ethiopia found only 15.0% of women knew that delivery in a health facility, HIV treatment and avoiding breastfeeding were methods to prevent MTCT to the infant [12]. …”
Section: Discussionmentioning
confidence: 99%
“…The following variables were considered to be potential confounders in the adjusted model based on previous findings of their association with HIV status, knowledge of MTCT and ANC use: age, place of residence, total number of live births in the last 5 years, education, and marital status [9-12]. All relevant variables were included as indicators in the unadjusted and adjusted models.…”
Section: Methodsmentioning
confidence: 99%